Effect of Colloid Centrifugation and Cold Storage of Boar Semen at 4 °C on Bacterial Load and Sperm Quality - CongBang Ngo; Jane M. Morrell; Ingrid Hansson; Padet Tummaruk; Aleksandar Cojkic (Antibiotics)
Background/Objectives: Alternatives to antibiotics in semen extenders used for pig breeding are needed. Cold storage of boar semen is possible in certain extenders; however, bacteria can still survive. Colloid centrifugation can remove bacteria; therefore, a combination of colloid centrifugation and cold storage on the bacterial load and sperm quality of boar semen was investigated. Results: The sperm quality in the original samples were similar in samples with and without antibiotics, respectively. At Day 4, the bacterial count was not different between controls stored at 17 °C with antibiotics and SLC cold-stored samples without antibiotics. The proportion of dead sperm increased in controls at 16–18 °C (28.12 ± 21.72% vs. 32.88 ± 20.94%; p < 0.05), and DNA fragmentation increased from 1.5 ± 1.02% at Day 0 to 6.1 ± 3.64% at Day 4 (p < 0.01), whereas it did not deteriorate in the cold-stored samples (Day 4: %DFI 2.00 ± 1.65% and 1.90 ± 1.05% for SLC samples with and without antibiotics, respectively). Methods: Aliquots of boar ejaculates were extended in Androstar Premium with and without antibiotics. The samples without antibiotics were processed by Single Layer Centrifugation (SLC) through Porcicoll; sperm pellets were resuspended in AndroStar Premium, with or without antibiotics, cooled slowly, and stored for 4 days at 4 °C. Controls (aliquots extended in AndroStar Premium with antibiotics) were stored at 17 °C. The bacterial load and sperm quality were assessed in the original samples and after 4 days of storage. Conclusions: Single Layer Centrifugation combined with cold storage is an effective method for reducing the bacterial load in boar semen, with or without antibiotics.